2022
DOI: 10.1093/eurpub/ckab218
|View full text |Cite
|
Sign up to set email alerts
|

Burden of non-communicable disease studies in Europe: a systematic review of data sources and methodological choices

Abstract: Background Assessment of disability-adjusted life years (DALYs) resulting from non-communicable diseases (NCDs) requires specific calculation methods and input data. The aims of this study were to: (i) identify existing NCD burden of disease (BoD) activities in Europe; (ii) collate information on data sources for mortality and morbidity; and (iii) provide an overview of NCD-specific methods for calculating NCD DALYs. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Methodological design choices of burden of infectious disease studies are more consistent compared to those that have been used in non-communicable and injury burden of disease studies [29,30]. An explanation for this finding may be that most of the studies that were included in our review were from the same country and mostly the same research teams.…”
Section: Summary Of Findings and Interpretation Of Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Methodological design choices of burden of infectious disease studies are more consistent compared to those that have been used in non-communicable and injury burden of disease studies [29,30]. An explanation for this finding may be that most of the studies that were included in our review were from the same country and mostly the same research teams.…”
Section: Summary Of Findings and Interpretation Of Resultsmentioning
confidence: 90%
“…These studies have varied in terms of scope and methodologies applied. Previous systematic reviews of burden of disease studies, focused on non-communicable diseases and injuries, have revealed considerable variations in methodological approaches used in independent disease burden studies [27][28][29][30][31]. Insight into these variations in methods is important since it affects the calculation, interpretation, and comparability.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, there is no standardized way of evaluating DALYs calculations or disease models currently in place. Thus for this review, we had to come up with an approach ourselves, which was inspired by previous literature along with the work done by the European Burden of Disease Network [51].…”
Section: Discussionmentioning
confidence: 99%
“…The systematic review of Haagsma et al [20] was used as a blueprint when creating the data extraction grid; in particular, the same categories proposed by Haagsma et al [20] were used when collecting incidence and prevalence data. Additionally, the data extraction sheet from Charalampous et al [25] was adopted in order to better fit the aim of this review and the disease. The data extraction was piloted with the FERG study [14], and no revision of the extraction table was necessary for this review.…”
Section: Data Screening Selection and Extractionmentioning
confidence: 99%
“…Finally, there is no standardized way of evaluating DALYs calculations or disease models currently in place. Thus for this review, we had to come up with an approach ourselves, which was inspired by previous literature along with the work done by the European Burden of Disease Network [25].…”
Section: Limitationsmentioning
confidence: 99%